Chitosan Beads Incorporated with Essential Oil of Thymus Capitatus: Stability Studies on Red Tilapia Fillets - Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Red Tilapia is one of the most consumed but perishable fish in the world. As a result, it requires preservation methods for safe consumption without affecting its organoleptic characteristics. Chitosan encapsulating essential oils have shown to be an excellent food conservation method. For that reason, we carried out the study of the protective effect on red Tilapia fillets with chitosan beads (CB) incorporated with Thymus capitatus (TCEO) essential oil at 500, 1000, and 2000 mg/L to assess the conservation of the fillets. The TCEO composition was characterized by gas chromatography-mass spectrometry (CG-MS). For the other side, CB was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction spectroscopy (XRD), thermogravimetric analysis (TGA), and Scanning electron microscopy (SEM). The protective effect of the beads was tested against the Gram-positive and Gram-negative bacteria growth for four weeks. The results showed an inhibition effect in Gram-positive bacteria at higher TCEO concentration (1000 and 2000 mg/L). Besides that, the pH, total volatile basic nitrogen (T-BNV-N), color, and fillet texture were evaluated as quality attributes. The results suggested that the incorporation of the CB-TCEO allowed a higher contact of the active compounds with the food surface, which reflected more excellent stability. The quality attributes of the fillets were preserved for 26 days, suggesting its uses for the treatment for perishable food. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.